Aqueous treatment media and methods of treating glass articles therewith

By using an aqueous treatment medium, including water, acids, salts, fluorine-containing compounds and saturated silica, the problem of textured surface formation in the prior art glass products is solved, and the formation of textured surfaces that are environmentally friendly, economical and suitable for mass production is achieved, and the adhesion of the coating is improved and the friction coefficient is reduced.

CN119731133APending Publication Date: 2025-03-28CORNING INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380060293.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-25
Filing Date
2023-08-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively form textured surfaces on glass products in large-scale production, and the use of inorganic acid solutions has problems of high capital costs and environmental pollution.

Method used

An aqueous treatment medium containing water, acids, salts, fluorine-containing compounds and saturated silica is used to contact the surface of the glass product to achieve etching and deposition of silica, thereby forming a textured surface.

Benefits of technology

This method can form an environmentally friendly textured surface on the glass product that is suitable for mass production, improve the adhesion of the coating, and reduce the friction coefficient of the glass product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731133A_ABST
    Figure CN119731133A_ABST
Patent Text Reader

Abstract

The aqueous treatment medium may include water; an acid selected from the group consisting of HCl, HBr, HNO3, H2SO4, H2SO3, H3PO4, H3PO2, HOAc, citric acid, tartaric acid, ascorbic acid, EDTA, methanesulfonic acid, toluenesulfonic acid, and compositions thereof, wherein the concentration of the acid in the aqueous treatment medium is 0.5 M to 1.5 M; a salt, wherein the concentration of the salt in the aqueous treatment medium is greater than 0 M to 2 M; a fluorine-containing compound selected from the group consisting of HF, NaF, NH4HF2, and the above compositions, wherein the concentration of the fluorine-containing compound in the aqueous treatment medium is 0.026 M to 0.26 M; and silica, wherein the aqueous treatment medium is saturated impregnated silica.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-referenced related applications

[0002] This application claims the priority benefit of U.S. Provisional Application No. 63 / 400,846 filed on August 25, 2022, in accordance with patent law regulations. This application relies on the content of the provisional application and the entire content of the provisional application is incorporated herein by reference.

[0003] field

[0004] The present description relates generally to aqueous media, and more particularly to aqueous media for etching glass articles. Background Art

[0005] Creating a textured surface on a glass article can increase the surface area of ​​the glass article and can improve the adhesion of coatings to the glass article. Various coatings can protect glass articles from damage caused by frictional contact. Methods for increasing the surface area of ​​glass articles containing silica may be limited by the ability to continuously dissolve silica from the surface of the glass article. On a laboratory scale, inorganic acid solutions (including hydrofluoric acid and boric acid) can be used to dissolve silica from the glass surface; however, the use of such acids may not be suitable for large-scale production operations due to high capital costs and environmental concerns.

[0006] Therefore, there is a need for alternative methods of forming textured surfaces on glass articles that are more environmentally friendly and suitable for large-scale production operations. Summary of the invention

[0007] According to a first aspect of the present invention, the aqueous treatment medium comprises water; an acid selected from the group consisting of HCl, HBr, HNO3, H2SO4, H2SO3, H3PO4, H3PO2, HOAc, citric acid, tartaric acid, ascorbic acid, EDTA, methanesulfonic acid, toluenesulfonic acid and a combination thereof, wherein the concentration of the acid in the aqueous treatment medium is 0.5M to 1.5M; a salt, wherein the concentration of the salt in the aqueous treatment medium is greater than 0M to 2M; a fluorine-containing compound selected from the group consisting of HF, NaF, NH4HF2 and a combination thereof, wherein the concentration of the fluorine-containing compound in the aqueous treatment medium is 0.026M to 0.26M; and silica, wherein the aqueous treatment medium is saturated with silica.

[0008] A second aspect of the present invention may include the first aspect, wherein the acid comprises citric acid.

[0009] A third aspect of the present invention may include the first aspect or the second aspect, wherein the salt comprises an alkali metal salt.

[0010] A fourth aspect of the present invention may include any one of the first to third aspects, wherein the salt comprises sodium chloride.

[0011] A fifth aspect of the present invention may include any one of the first to fourth aspects, wherein the salt comprises aluminum chloride.

[0012] A sixth aspect of the present invention may include any one of the first to fifth aspects, wherein the salt comprises sodium chloride and aluminum chloride.

[0013] A seventh aspect of the present invention may include the sixth aspect, wherein the ratio of aluminum to sodium is from 1:1 to 3:1.

[0014] An eighth aspect of the present invention may include any one of the first to seventh aspects, wherein the fluorine-containing compound comprises NH4HF2.

[0015] A ninth aspect of the present invention may include any one of the first to eighth aspects, wherein the acid comprises citric acid, the salt comprises sodium chloride, aluminum chloride or a combination thereof, and the fluorine-containing compound comprises NH4HF2.

[0016] According to a tenth aspect of the present invention, a method for treating a glass article may include contacting a surface of the glass article with an aqueous treatment medium to form a treated surface of the glass article. The glass article comprises silica. The aqueous treatment medium comprises water; an acid selected from the group consisting of HCl, HBr, HNO3, H2SO4, H2SO3, H3PO4, H3PO2, HOAc, citric acid, tartaric acid, ascorbic acid, EDTA, methanesulfonic acid, toluenesulfonic acid, and combinations thereof, wherein the concentration of the acid in the aqueous treatment medium is 0.5M to 1.5M; a salt, wherein the concentration of the salt in the aqueous treatment medium is greater than 0M to 2M; a fluorine-containing compound selected from the group consisting of HF, NaF, NH4HF2, and combinations thereof, wherein the concentration of the fluorine-containing compound in the aqueous treatment medium is 0.026M to 0.26M; and silica, wherein the aqueous treatment medium is saturated with silica. The aqueous treatment medium etches silica from the surface of the glass article and deposits silica onto the surface of the glass article.

[0017] An eleventh aspect of the present invention may include the tenth aspect, wherein the glass article is formed of Type I Class A or Type I Class B glass in accordance with ASTM Standard E438-92.

[0018] A twelfth aspect of the present invention may include the tenth aspect or the eleventh aspect, wherein the glass article is formed of borosilicate glass.

[0019] A thirteenth aspect of the present invention may include any one of the tenth to twelfth aspects, wherein the glass article is an ion-exchange strengthened glass article including a surface compressive stress layer.

[0020] A fourteenth aspect of the present disclosure may include any of the tenth to thirteenth aspects, wherein the glass article is a glass container and includes a sidewall at least partially surrounding an interior volume, the sidewall having an exterior surface.

[0021] A fifteenth aspect of the present invention may include the fourteenth aspect, wherein the aqueous treatment medium contacts an outer surface of the side wall.

[0022] A sixteenth aspect of the present invention may include any one of the tenth to fifteenth aspects, wherein contacting the glass article with the aqueous treatment medium is performed for a period of 5 minutes to 72 hours.

[0023] A seventeenth aspect of the present invention may include any one of the tenth to sixteenth aspects, wherein contacting the glass article with the aqueous treatment medium is performed at a temperature between ambient temperature and 50°C.

[0024] An eighteenth aspect of the present invention may include any one of the tenth to seventeenth aspects, wherein the method further comprises rinsing at least the treated surface of the glass article with deionized water.

[0025] A nineteenth aspect of the present invention may include any one of the tenth to eighteenth aspects, wherein the treated surface of the glass article comprises silica deposits having a height of greater than 0 nanometers (nm) to 20 nm and a diameter of greater than 0 nm to 50 nm.

[0026] A twentieth aspect of the present invention may include any one of the tenth to eighteenth aspects, wherein the method further comprises applying a low friction coating to the treated surface of the glass article.

[0027] According to the twenty-first aspect of the present invention, a method for preparing an aqueous treatment medium comprises: heating a mixture to a temperature of 25°C to 95°C, the mixture comprising water; an acid selected from the group consisting of HCl, HBr, HNO3, H2SO4, H2SO3, H3PO4, H3PO2, HOAc, citric acid, tartaric acid, ascorbic acid, EDTA, methanesulfonic acid, toluenesulfonic acid and combinations thereof; a fluorine-containing compound selected from the group consisting of HF, NaF, NH4HF2 and combinations thereof; and silica powder; cooling the mixture to ambient temperature; filtering out undissolved silica powder from the mixture; and adding one or more salts to the mixture to form an aqueous treatment medium.

[0028] A twenty-second aspect of the present invention may include the twenty-first aspect, wherein the water is deionized water.

[0029] A twenty-third aspect of the present invention may include the twenty-first aspect or the twenty-second aspect, wherein the acid comprises citric acid.

[0030] A twenty-fourth aspect of the present invention may include any one of aspects twenty-first to twenty-third, wherein the salt comprises an alkali metal salt.

[0031] A twenty-fifth aspect of the present invention may include any one of aspects twenty-first to twenty-fourth, wherein the salt comprises sodium chloride.

[0032] A twenty-sixth aspect of the present invention may include any one of aspects twenty-first to twenty-fifth, wherein the salt comprises aluminum chloride.

[0033] A twenty-seventh aspect of the present invention may include any one of aspects twenty-first to twenty-sixth, wherein the salt comprises sodium chloride and aluminum chloride.

[0034] A twenty-eighth aspect of the present invention may include the twenty-seventh aspect, wherein the ratio of aluminum to sodium is from 1:1 to 3:1.

[0035] A twenty-ninth aspect of the present invention may include any one of aspects twenty-first to twenty-eighth, wherein the fluorine-containing compound comprises NH4HF2.

[0036] A thirtieth aspect of the present invention may include any one of the twenty-first to twenty-ninth aspects, wherein the silica powder comprises silica particles having a particle size of 100 nm to 1000 nm.

[0037] The thirty-first aspect of the present invention may include any one of the twenty-first to thirtieth aspects, wherein the acid comprises citric acid, the salt comprises sodium chloride, aluminum chloride or a combination thereof, and the fluorine-containing compound comprises NH4HF2.

[0038] A thirty-second aspect of the present invention may include any one of aspects twenty-first to thirty-first, wherein the concentration of the acid in the aqueous treatment medium is 0.5M to 1.5M.

[0039] A thirty-third aspect of the present invention may include any one of aspects twenty-first to thirty-second, wherein the concentration of the salt in the aqueous treatment medium is greater than 0M to 2M.

[0040] A thirty-fourth aspect of the present invention may include any one of aspects twenty-first to thirty-third, wherein the concentration of the fluorine-containing compound in the aqueous treatment medium is from 0.026M to 0.26M.

[0041] A thirty-fifth aspect of the present invention may include any one of aspects twenty-first to thirty-fourth, wherein the aqueous treatment medium is saturated silica.

[0042] Additional features and advantages of the present invention will be described in detail below, and will become more apparent to those skilled in the art after reviewing or practicing the embodiments described herein, including the following detailed description of the embodiments, the claims, and the accompanying drawings.

[0043] It should be understood that the above summary and the following detailed description are descriptions of various embodiments and are intended to provide an overview or framework to understand the nature and characteristics of the claimed object. The included drawings provide a further understanding of the various embodiments and are therefore incorporated into and constitute a part of this specification. The drawings depict the various embodiments and together with the description of the embodiments are used to explain the principles and operations of the claimed object. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 schematically depicts a glass container according to one or more embodiments;

[0045] Figure 2 A scanning electron microscope (SEM) image of the surface of a sample bottle etched by an aqueous treatment medium sample 1 according to an embodiment of Example 2 is shown;

[0046] Figure 3 FIG. 4 is a SEM image of the surface of a sample bottle etched by an aqueous treatment medium sample 9 according to an embodiment of Example 2;

[0047] Figure 4 FIG. 4 is a SEM image of a surface of a sample bottle etched by an aqueous treatment medium sample 18 according to an embodiment of Example 2;

[0048] Figure 5 FIG. 4 is a SEM image of a surface of a sample bottle etched by an aqueous treatment medium sample 19 according to an embodiment of Example 2;

[0049] Figure 6 A confocal image of the surface of a sample bottle etched by an aqueous treatment medium sample 1 according to the embodiment of Example 2 is shown;

[0050] Figure 7 A confocal image of the surface of a sample bottle etched by an aqueous treatment medium sample 9 according to the embodiment of Example 2 is shown;

[0051] Figure 8 A confocal image of the surface of a sample bottle etched by an aqueous treatment medium sample 17 according to the embodiment of Example 2 is shown;

[0052] Fig. 9 A confocal image of the surface of a sample bottle etched by an aqueous treatment medium sample 24 according to the embodiment of Example 2 is shown;

[0053] Fig.10 An atomic force microscope (AFM) image of the surface of a sample bottle etched by an aqueous treatment medium sample 1 according to an embodiment of Example 2 is shown;

[0054] Fig.11FIG. 4 shows an AFM image of the surface of a sample bottle etched by an aqueous treatment medium sample 5 according to an embodiment of Example 2;

[0055] Fig.12 An AFM image of the surface of a sample bottle etched by an aqueous treatment medium sample 11 according to the embodiment of Example 2 is shown; and

[0056] Fig.13 The graph shows the coefficient of friction data of the coated sample bottles according to the embodiment of Example 3. DETAILED DESCRIPTION

[0057] Reference will now be made in detail to various embodiments of aqueous treatment media for treating glass articles. Identical or similar parts are indicated by the same reference numerals in the various figures whenever possible. In embodiments, the aqueous treatment medium may include water, acids, salts, fluorine-containing compounds, and silica. The aqueous treatment medium embodiments may be used in methods for treating glass articles, wherein the methods include contacting a surface of the glass article with the aqueous treatment medium to form a treated surface of the glass article. Embodiments of the aqueous treatment medium and methods for making and using the same are further described herein.

[0058] Ranges may be expressed herein as from "about" one particular value and / or to "about" another particular value. When a range is expressed in this manner, another embodiment includes from one particular value and / or to another particular value. Similarly, when a value is expressed as an approximation with the antecedent "about," it is understood that the particular value may constitute another embodiment. It is further understood that the endpoints of each range are meaningful relative to the other endpoint and are independent of the other endpoint.

[0059] As used herein, the singular forms "a", "an" and "the" include plural references unless the context clearly dictates otherwise. Thus, reference to "a" component includes aspects having two or more such components unless the context clearly dictates otherwise.

[0060] Glass articles, including glass containers, can be coated to protect the glass articles from damage, including damage caused by frictional contact between glass articles. Forming a textured surface on a glass article can improve the adhesion of the coating to the surface of the glass article. Conventional methods for texturing the surface of a glass article can include dissolving silica from the surface of the glass article. On a laboratory scale, inorganic acid solutions (e.g., solutions including hydrofluoric acid and boric acid) can be used to dissolve silica from the surface of the glass. However, due to high capital costs and environmental considerations, the use of such solutions may not be suitable for large-scale production operations to manufacture textured surfaces on glass articles. Therefore, there is a need for alternative methods for forming textured surfaces on glass articles that are more environmentally friendly and suitable for large-scale production operations. The aqueous treatment medium embodiments described herein are suitable for large-scale production operations and are more environmentally friendly than conventional etching solutions. Without being bound by theory, the aqueous treatment medium embodiments described herein are more environmentally friendly due to the relatively low fluoride content and are compatible with large-scale production operations.

[0061] In embodiments, the aqueous treatment medium may include water. By way of non-limiting example, the water may include one or more of deionized water, tap water, distilled water, or fresh water. In embodiments, one or more components of the aqueous treatment medium may be soluble in water.

[0062] The aqueous treatment medium may include an acid. The acid may be selected from the group consisting of HCl, HBr, HNO3, H2SO4, H2SO3, H3PO4, H3PO2, HOAc, citric acid, tartaric acid, ascorbic acid, EDTA, methanesulfonic acid, toluenesulfonic acid, and combinations thereof. In embodiments, the aqueous treatment medium may include more than one acid. For example, the aqueous treatment medium may include 2, 3, 4, 5 or more acids. In embodiments, the acid may include citric acid. In embodiments, the acid may consist essentially of or consist of citric acid.

[0063] In an embodiment, the concentration of the acid in the aqueous treatment medium may be 0.5 volume molar (M) to 1.5 M. By way of non-limiting example, the concentration of the acid in the aqueous treatment medium may be 0.5 M to 1.5 M, 0.7 M to 1.5 M, 0.9 M to 1.5 M, 1.1 M to 1.5 M, 1.3 M to 1.5 M, 0.5 M to 1.3 M, 0.5 M to 1.1 M, 0.5 M to 0.9 M, 0.5 M to 0.7 M, or any combination or subset of these ranges.

[0064] Without intending to be bound by theory, when the acid comprises one or more of HCl, HBr, HNO3, H2SO4, H2SO3, H3PO4, H3PO2, HOAc, citric acid, tartaric acid, ascorbic acid, EDTA, methanesulfonic acid, toluenesulfonic acid, and the concentration of the acid is 0.5 M to 1.5 M, the acid can operate to dissolve silica from a portion of the surface of the glass article without removing silica from other portions of the surface of the glass article. This can impart a surface texture to the glass article that contacts the aqueous treatment medium without damaging the structure of the glass article.

[0065] The aqueous treatment medium may contain salts. In embodiments, the concentration of the salt in the aqueous treatment medium may be greater than 0 M to 2 M. For example, the concentration of the salt in the aqueous treatment medium may be greater than 0 M to 2.0 M, greater than 0 M to 1.8 M, greater than 0 M to 1.6 M, greater than 0 M to 1.4 M, greater than 0 M to 1.2 M, greater than 0 M to 1.0 M, greater than 0 M to 0.8 M, greater than 0 M to 0.6 M, greater than 0 M to 0.4 M, greater than 0 M to 0.2 M, 0.2 M to 2.0 M, 0.4 M to 2.0 M, 0.6 M to 2.0 M, 0.8 M to 2.0 M, 1.0 M to 2.0 M, 1.2 M to 2.0 M, 1.4 M to 2.0 M, 1.6 M to 2.0 M, 1.8 M to 2.0 M, or any combination or subset of such ranges.

[0066] In an embodiment, the salt may comprise an alkali metal salt. As described herein, "alkali metal salts" comprise alkali metals, Group 1 metals according to IUPAC nomenclature, including lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), and fernandinium (Fr). By way of non-limiting example, the salt may comprise sodium chloride or potassium chloride. In an embodiment, the salt may comprise sodium chloride. In an embodiment, the salt may comprise other metal salts other than alkali metal salts, such as aluminum chloride. In an embodiment, the aqueous treatment medium may comprise a plurality of salts. By way of non-limiting example, the aqueous treatment medium may comprise 2, 3, 4, 5 or more salts. In an embodiment, the aqueous treatment medium may comprise sodium chloride and aluminum chloride. In such embodiments, the aluminum to sodium molar ratio may be 1:1 to 3:1. By way of non-limiting example, the aluminum to sodium molar ratio can be 1:1 to 3:1, 1.5:1 to 3:1, 2:1 to 3:1, 2.5:1 to 3:1, 1:1 to 2.5:1, 1:1 to 2:1, 1:1 to 1.5:1, or any combination or subset of such ranges. Without intending to be bound by theory, the inclusion of a salt in the aqueous treatment medium can adjust the etch rate of the glass article treated with the medium.

[0067] Without intending to be bound by theory, the concentration of salts in the aqueous treatment medium can affect the degree of texturing of the surface area of ​​the glass article contacting the aqueous treatment medium. For example, as the concentration of salts in the aqueous treatment medium increases, the density and size of silica deposits on the surface of the glass article treated with the aqueous treatment medium increase.

[0068] The aqueous treatment medium may further comprise a fluorine-containing compound. The fluorine-containing compound is selected from the group consisting of HF, NaF, NH4HF2, and combinations thereof. In embodiments, the aqueous treatment medium may comprise a plurality of fluorine-containing compounds. By way of non-limiting example, the aqueous treatment medium may comprise 2 or 3 fluorine-containing compounds. In embodiments, the fluorine-containing compound comprises NH4HF2. In embodiments, the fluorine-containing compound may consist essentially of NH4HF2 or consist of NH4HF2. Without intending to be bound by theory, the fluorine-containing compound may be soluble in the aqueous treatment medium and serve as a source of fluoride ions in the aqueous treatment medium.

[0069] In an embodiment, the concentration of the fluorine-containing compound in the aqueous treatment medium is 0.026 M to 0.26 M. By way of non-limiting example, the concentration of the fluorine-containing compound in the aqueous treatment medium may be 0.026 M to 0.26 M, 0.05 M to 0.26 M, 0.10 M to 0.26 M, 0.15 M to 0.26 M, 0.20 M to 0.26 M, 0.026 M to 0.20 M, 0.026 M to 0.15 M, 0.026 M to 0.10 M, 0.026 M to 0.05 M, or any combination or subset of these ranges.

[0070] Without intending to be bound by theory, the concentration of the fluorine-containing compound may affect the degree of texturing of the surface area of ​​the glass article contacting the aqueous treatment medium. For example, as the concentration of the fluorine-containing compound in the aqueous treatment medium increases, the density and size of silica deposits on the surface of the glass article contacting the aqueous treatment medium increase.

[0071] The aqueous treatment medium further comprises silica (SiO2). In embodiments, the aqueous treatment medium may be saturated with silica. As described herein, the aqueous treatment medium may be saturated with silica when the silica is no longer soluble in the aqueous treatment medium. The amount of silica required to saturate the aqueous treatment medium may vary depending on the temperature of the aqueous treatment medium, the holding pressure of the aqueous treatment medium, and the concentration of acids, salts, and fluorides in the aqueous treatment medium.

[0072] Without intending to be bound by theory, an aqueous treatment medium saturated with silica allows silica to dissolve from the surface of the glass article in the aqueous treatment medium and deposit from the aqueous treatment medium onto the surface of the glass article, thereby imparting a surface texture to the glass article. This effect may occur because locally unsaturated silica in the aqueous treatment medium may cause partial surface dissolution of the glass article, while locally oversaturated silica in the aqueous treatment medium may cause silica to deposit from the aqueous treatment medium onto the surface of the glass article. Dissolution of silica from the surface of the glass article may leave depressions on the surface of the glass article, and deposition of silica onto the surface of the glass article may produce protrusions on the surface of the glass article. Therefore, a glass article containing silica may be textured by exposing the glass article to an aqueous treatment medium saturated with silica.

[0073] Now turning to the description of the method for making an aqueous treatment medium. In an embodiment, the method for making an aqueous treatment medium may include heating a mixture comprising water, an acid, and silica powder to a temperature of 25°C to 95°C. For example, the mixture may be heated to the following temperatures: 25°C to 95°C, 35°C to 95°C, 45°C to 95°C, 55°C to 95°C, 65°C to 95°C, 75°C to 95°C, 85°C to 95°C, 25°C to 85°C, 25°C to 75°C, 25°C to 65°C, 25°C to 55°C, 25°C to 45°C, 25°C to 35°C, or any combination or subset of such ranges. Without intending to be bound by theory, heating the mixture may increase the solubility of silica in the mixture and the dissolution rate of silica powder in the mixture.

[0074] The water may be any of the waters described above with respect to the aqueous treatment medium. In an embodiment, the water may be deionized water. As previously described, the acid may be selected from the group consisting of HCl, HBr, HNO3, H2SO4, H2SO3, H3PO4, H3PO2, HOAc, citric acid, tartaric acid, ascorbic acid, EDTA, methanesulfonic acid, toluenesulfonic acid, and combinations thereof.

[0075] In an embodiment, the silica powder may include silica particles having an average particle size of 100 nm to 1000 nm. By way of non-limiting example, the average particle size of the silica particles may be 100 nm to 1000 nm, 300 nm to 1000 nm, 500 nm to 1000 nm, 700 nm to 1000 nm, 900 nm to 1000 nm, 100 nm to 800 nm, 100 nm to 600 nm, 100 nm to 400 nm, 100 nm to 200 nm, or any combination or subset of such ranges. Without intending to be bound by theory, when the average particle size of the silica particles is 100 nm to 1000 nm, the silica can be easily dissolved in the aqueous treatment medium, and once the aqueous treatment medium is saturated with silica, any undissolved particles can be filtered out of the aqueous treatment medium.

[0076] The method for making an aqueous treatment medium may include cooling the mixture to ambient temperature after heating. Cooling may be achieved by any suitable means, including, but not limited to, active cooling and passive cooling. In an embodiment, the mixture is passively cooled to ambient temperature. Without intending to be bound by theory, as the mixture cools, the solubility of silica in the mixture decreases. Allowing silica to dissolve in the mixture at an elevated temperature and then cooling the mixture may help to produce a mixture saturated with silica at a cooler temperature. It should be noted that during the cooling step, silica may precipitate from the mixture.

[0077] In an embodiment, the method for making an aqueous treatment medium may include filtering out undissolved silica powder from the mixture. The undissolved silica powder may be filtered out by any filtering means operable to remove undissolved silica particles having an average particle size of 100 nm to 1000 nm. By way of non-limiting example, suitable filtering means may include filter paper and gauze, depending on the particle size to be removed from the aqueous treatment medium. Without intending to be bound by theory, unfiltered silica particles may contact the glass surface, causing visible defects on the glass surface. Filtering out excess silica particles from the aqueous treatment medium may avoid contact between the silica particles and the glass surface contacting the aqueous treatment medium.

[0078] The method for making an aqueous treatment medium may include adding one or more salts to a mixture to form an aqueous treatment medium. The salt may be any of the salts described above with respect to the composition of the aqueous treatment medium. In embodiments, the salt may include sodium chloride, aluminum chloride, or a combination thereof. It should be understood that embodiments of the aqueous treatment medium formed by the methods described herein may have the aforementioned composition.

[0079] Now turn to the description of the method for treating a glass article with an aqueous treatment medium. In an embodiment, as described above, the method for treating a glass article may include contacting a surface of the glass article with an aqueous treatment medium. In an embodiment, the glass article includes silica. The aqueous treatment medium may etch silica from the surface of the glass article and deposit silica onto the surface of the glass article to impart a texture to the treated surface of the glass article.

[0080] In an embodiment, the glass article may be formed of a glass composition that meets the Type I Class A (Type IA) or Type I Class B (Type IB) glass standards according to ASTM standard E438-92 (2011), entitled "Standard Specification for Glasses in Laboratory Apparatus". In an embodiment, the glass may be a borosilicate glass that meets these standards or an aluminosilicate glass that meets the same standards (except for the composition). Borosilicate glass meets the Type I (A or B) standards and is commonly used in pharmaceutical packaging. Examples of borosilicate glass include, but are not limited to 7740, 7800, Wheaton180, 200 and 400, Schott Schott N-51A, Gerresheimer GX-51Flint, etc. Example aluminosilicate glasses include those from Corning It should be understood that the methods described herein can be used with other glass compositions, including borosilicate and aluminosilicate glasses that do not meet the above criteria.

[0081] In embodiments, the glass article may be an ion exchange strengthened glass article comprising a surface compressive stress layer. In embodiments, the ion exchange strengthened glass article may have a compressive stress of greater than or equal to about 250 megapascals (MPa), 300 MPa, or even greater than or equal to about 350 MPa at the surface of the ion exchange strengthened glass article. In embodiments, the compressive stress of the glass surface may be greater than or equal to about 400 MPa, or even the glass surface may be greater than or equal to about 450 MPa. In some embodiments, the compressive stress of the glass surface may be greater than or equal to about 500 MPa, or even the glass surface may be greater than or equal to about 550 MPa. In still other embodiments, the compressive stress of the glass surface may be greater than or equal to about 650 MPa, or even the glass surface may be greater than or equal to about 750 MPa. The compressive stress of the ion exchange strengthened glass article generally extends to a depth of layer (DOL) of at least about 10 micrometers (μm). In some embodiments, the ion exchange strengthened glass article may have a depth of layer greater than about 25 μm, or even greater than about 50 μm. In some other embodiments, the layer depth may be as high as about 75 μm or even about 100 μm. Ion exchange strengthening may be performed in a molten salt bath maintained at a temperature of about 350° C. to about 600° C. To achieve the desired compressive stress, the glass article may be immersed in the salt bath for less than about 30 hours or even less than about 20 hours. In an embodiment, the glass article may be immersed for less than about 15 hours or even less than about 12 hours. In other embodiments, the glass article may be immersed for less than about 10 hours. For example, in one embodiment, the glass article is immersed in a 100% KNO3 salt bath at about 450° C. for about 5 hours to about 8 hours to achieve the desired layer depth and compressive stress.

[0082] In embodiments, the glass article may be a glass container and include a glass body at least partially surrounding an interior volume, and a sidewall having an exterior surface. Figure 1 , for example, schematically illustrates a cross-section of a glass container, such as a glass container for storing a pharmaceutical composition. The glass container 100 generally comprises a glass article having a glass body 102. The glass body 102 extends between an inner surface 104 and an outer surface 106 and generally encloses an interior volume 108. Figure 1In the embodiment of the glass container 100 shown, the glass body 102 generally includes a wall portion 110 and a bottom portion 112. The wall portion 110 and the bottom portion 112 may generally have a thickness of about 0.5 millimeters (mm) to about 3.0 mm. The wall portion 110 transitions to the bottom portion 112 through a heel portion 114. Although the glass container 100 is Figure 1 Although depicted as having a particular shape (i.e., a sample bottle), it should be understood that the glass container 100 may have other shapes, including, but not limited to, vacuum blood collection tubes, cartridges, syringes, syringes, ampoules, flasks, vials, tubes, beakers, etc.

[0083] In embodiments, the aqueous treatment medium may contact the outer surface 106 of the glass body 102. In embodiments, the aqueous treatment medium may be prevented from contacting the inner surface 104 of the glass article. This may be accomplished by plugging or otherwise closing the opening of the glass container to prevent the aqueous solution from entering the interior volume 108 of the glass container 100.

[0084] In an embodiment, the glass article may be contacted with the aqueous treatment medium for a period of 5 minutes to 72 hours. By way of non-limiting example, the glass article may be contacted with the aqueous treatment medium for a period of 5 minutes to 72 hours, 30 minutes to 72 hours, 1 hour to 72 hours, 6 hours to 72 hours, 12 hours to 72 hours, 24 hours to 72 hours, 48 ​​hours to 72 hours, 5 minutes to 48 hours, 5 minutes to 24 hours, 5 minutes to 12 hours, 5 minutes to 6 hours, 5 minutes to 1 hour, 5 minutes to 30 minutes, or any combination or subset of these ranges.

[0085] In embodiments, the glass article may be contacted with the aqueous treatment medium at a temperature ranging from ambient temperature to 50°C. By way of non-limiting example, the glass article may be contacted with the aqueous treatment medium at a temperature ranging from ambient temperature to 50°C, 20°C to 50°C, 25°C to 50°C, 30°C to 50°C, 35°C to 50°C, 35°C to 50°C, 40°C to 50°C, 45°C to 50°C, 20°C to 45°C, 20°C to 40°C, 20°C to 35°C, 20°C to 30°C, 20°C to 25°C, or any combination or subset of such ranges. As used herein, "ambient temperature" refers to the ambient temperature of a particular location. By way of non-limiting example, the ambient temperature may be about 20°C. Without intending to be bound by theory, the temperature and time at which the glass article is contacted with the aqueous treatment medium to achieve a desired surface roughness may be inversely related. For example, as the temperature at which the glass article is contacted with the aqueous treatment medium increases, the time the glass article is contacted with the aqueous treatment medium may be reduced to achieve a desired surface roughness.

[0086] In embodiments, the method for treating a glass article may further comprise rinsing at least the treated surface of the glass article with water. In some embodiments, the water may be deionized water. Rinsing the surface of the glass article may remove the aqueous treatment medium from the treated surface of the glass article, stop etching silica from the treated surface of the glass article, or stop silica deposition onto the treated surface of the glass article.

[0087] In an embodiment, the treated surface of the glass article may include a silica deposit. In one or more embodiments, the silica deposit may be dome-shaped. The silica deposit may have a height greater than 0nm to 20nm. By way of non-limiting example, the height of the silica deposit may be greater than 0nm to 20nm, 5nm to 20nm, 10nm to 20nm, 15nm to 20nm, greater than 0nm to 15nm, greater than 0nm to 10nm, greater than 0nm to 5nm, or any combination or subset of such ranges. The height of the silica deposit may be measured by atomic force microscopy. The height of the silica deposit may be relative to the bottom surface of the glass article. In an embodiment, the silica deposit may have a diameter greater than 0nm to 50nm. By way of non-limiting example, the diameter of the silica deposit may be greater than 0 nm to 50 nm, 10 nm to 50 nm, 20 nm to 50 nm, 30 nm to 50 nm, 40 nm to 50 nm, greater than 0 nm to 40 nm, greater than 0 nm to 30 nm, greater than 0 nm to 20 nm, greater than 0 nm to 10 nm, or any combination or subset of such ranges. The diameter of the silica deposit may be measured by atomic force microscopy. Without intending to be bound by theory, the silica deposit on the treated glass surface may be bonded to the treated glass surface by a combination of van der Waals forces, hydrogen bonding, and capillary forces.

[0088] The method for treating the surface of a glass article may further include applying a low-friction coating to the treated surface of the glass article. The low-friction coating may be applied to the treated surface by any suitable means, such as spraying the low-friction coating onto the treated surface. The low-friction coating reduces the coefficient of friction of the main body portion having the coating, thereby reducing the wear and surface damage of the outer surface of the glass body. In essence, the coating enables the container to "slide" relative to another object (or container), thereby reducing the possibility of damage to the glass surface. Furthermore, the low-friction coating can also act as a buffer for the main body of the glass container, thereby reducing the damage caused by blunt impact to the glass container. Suitable coatings are disclosed in U.S. Patent Application No. 13 / 780,754 filed on February 28, 2013 and U.S. Patent Application No. 14 / 075,630 filed on November 8, 2013, and the entire contents of each application are incorporated herein by reference. However, it should be understood that other types of coatings can be applied to the treated surface of the glass article.

[0089] As described above, the coating may have a low coefficient of friction. The coefficient of friction (μ) of the coated glass container portion with the low friction coating may be lower than the coefficient of friction of the surface of the uncoated glass container formed of the same material. The coefficient of friction (μ) is a quantitative friction measurement between two surfaces and is a function of the mechanical and chemical properties of the first and second surfaces, including surface roughness and environmental conditions, such as, but not limited to, temperature and humidity. As used herein, the coefficient of friction measurement of the coated glass container is described as the coefficient of friction between the outer surface of the first glass container and the outer surface of the second glass container, the second glass container is identical to the first glass container, wherein the first and second glass containers have the same body and the same coating composition (when applied) and have been exposed to the same environment before, during and after manufacturing. Unless otherwise specified herein, the coefficient of friction refers to the maximum coefficient of friction measured on a bottle-to-bottle test stand using a 30 Newton (N) positive load. However, it should be understood that a coated glass container that exhibits a maximum coefficient of friction under a specific applied load will also exhibit the same or better (i.e., lower) maximum coefficient of friction under a smaller load. For example, if a coated glass container exhibits a maximum coefficient of friction of 0.5 or less under an applied load of 50N, the coated glass container will also exhibit a maximum coefficient of friction of 0.5 or less under an applied load of 25N.

[0090] In the described embodiment, the coefficient of friction of glass containers (coated and uncoated) is measured using a bottle-to-bottle test stand. This measurement technique and corresponding equipment are described in U.S. Patent Application No. 13 / 780,754 filed on February 28, 2013, the entire contents of which are incorporated herein by reference.

[0091] In the described embodiments, the portion of the coated glass container having the low friction coating has a coefficient of friction of less than or equal to about 0.7 relative to a similar coated glass container as measured by a bottle-to-bottle test rack. In other embodiments, the coefficient of friction may be less than or equal to about 0.6, or even less than or equal to about 0.5. In some embodiments, the portion of the coated glass container having the low friction coating has a coefficient of friction of less than or equal to about 0.4, or even less than or equal to about 0.3. Coated glass containers having a coefficient of friction of less than or equal to about 0.7 generally exhibit increased resistance to friction damage and thus have improved mechanical properties. For example, a conventional glass container (without a low friction coating) may have a coefficient of friction greater than 0.7.

[0092] In some of the embodiments described above, the coefficient of friction of the portion of the coated glass container having the low-friction coating is at least 20% less than the coefficient of friction of an uncoated glass container surface formed of the same glass composition. For example, the coefficient of friction of the portion of the coated glass container having the low-friction coating may be at least 20%, at least 25%, at least 30%, at least 40%, or even at least 50% less than the coefficient of friction of an uncoated glass container surface formed of the same glass composition.

[0093] Examples

[0094] The embodiments described herein will be further illustrated by the following examples.

[0095] Example 1 - Aqueous Process Media Sample

[0096] The aqueous treatment medium samples were prepared by heating a mixture of citric acid, ammonium bifluoride (NH4HF2) and silica fine powder in deionized water at 45°C for 24 hours. Each sample was saturated with silica (SiO2). The mixture was allowed to cool to room temperature and then filtered to remove undissolved silica. Various amounts of aluminum chloride (AlCl3) and sodium chloride (NaCl) salts were added to the mixture to form the aqueous treatment medium samples. The concentrations of citric acid, sodium chloride, aluminum chloride and ammonium bifluoride for each aqueous treatment medium sample are listed in Table 1.

[0097] Table 1: Composition of aqueous treatment media samples

[0098]

[0099]

[0100] Example 2 - Etching Glass Articles Using Aqueous Treatment Medium Samples

[0101] Corning ion exchange Glass pharmaceutical sample bottles were exposed to each aqueous treatment medium sample listed in Table 1. Each sample bottle was etched in the aqueous treatment medium sample bath at room temperature for 24 hours. Each sample bottle was then rinsed with deionized water and stored in deionized water.

[0102] The surface topography of each vial was characterized using an image of the vial captured under top-down illumination. The relative intensity of scattered light for each vial was measured based on the grayscale intensity of the vial image. The relative intensity of scattered light for each vial is listed in Table 2.

[0103] Table 2: Relative intensity of scattered light from each sample bottle

[0104]

[0105]

[0106] The sample bottles etched in the aqueous treatment medium samples without salts or containing aluminum chloride (Samples 1-3 and 10-18) appeared smooth and comparable to the reference sample bottles that were not exposed to the aqueous treatment medium samples. The sample bottles etched in the aqueous treatment medium samples including sodium chloride (Samples 4-9) included non-uniform macro-deposits on the sample bottle surfaces that were exposed to the aqueous medium. The density and size of these deposits increased with increasing ammonium bifluoride concentration. For example, the sample bottle etched with Sample 6 included larger deposits on the sample bottle surface than the sample bottle etched with Sample 4. The sample bottles etched with the mixed salt aqueous treatment medium samples (wherein the ammonium bifluoride concentration was 0.26M (Samples 21 and 24)) exhibited macro-deposits; however, when the ammonium bifluoride concentration was 0.13M or 0.026M (Samples 19-20 and 22-23), the surface of the sample bottles appeared smooth.

[0107] The surface morphology of the sample bottles etched with the aqueous treatment medium samples was observed using a scanning electron microscope (SEM). Figure 2 The SEM image of the surface of the sample bottle etched by the aqueous treatment medium sample 1 is shown. Figure 3 The SEM image of the surface of the sample bottle etched by the aqueous treatment medium sample 9 is shown. Figure 4 The SEM image of the surface of the sample bottle etched by the aqueous treatment medium sample 18 is shown. Figure 5 SEM images of the surface of a sample bottle etched with aqueous treatment medium Sample 19 are shown. The macro deposits observed on the sample bottle etched with aqueous treatment medium Sample 9 were identified as crystalline formations with a composition similar to that of the base glass. The sample bottle etched with the mixed salt solution of Sample 19 had unevenly distributed pits on the treated surface of the sample bottle, indicating that glass material had been removed from the glass surface.

[0108] The surface morphology of the sample vials etched with the aqueous treatment medium samples was quantified using confocal imaging. Figure 6 A confocal image of the surface of a sample bottle etched with aqueous treatment medium sample 1 is shown. Figure 7 A confocal image of the surface of a sample bottle etched with an aqueous treatment medium sample 9 is shown. Figure 8 A confocal image of the surface of a sample bottle etched with an aqueous treatment medium sample 17 is shown. Fig. 9 A confocal image of the surface of a sample vial etched with aqueous treatment medium sample 24 is shown. Statistical analysis of the surface roughness showed that the sample vial surface was highly sensitive to the interaction between the ammonium bifluoride concentration and the ratio of aluminum chloride to sodium chloride salts in the aqueous treatment medium.

[0109] The surfaces of the sample vials treated with the aqueous treatment medium samples were analyzed using atomic force microscopy (AFM). Typically, AFM can characterize feature sizes with a spatial resolution of approximately 10 nm. Fig.10An AFM image of the surface of a sample bottle etched with aqueous treatment medium sample 1 is shown. Fig.11 An AFM image of the surface of a sample bottle etched with aqueous treatment medium sample 5 is shown. Fig.12 An AFM image of the surface of a sample bottle etched with an aqueous treatment medium sample 11 is shown. Fig.12 Depth and height graphs of silica deposits and pits on the surface of the sample vials etched with sample 11 are shown. When the sample vials (samples 1-3) were etched with the aqueous treatment medium sample without salt, the thickness of the deposited particles was about 10 nm. The sample vials (samples 10-24) were etched with the aqueous treatment medium sample including aluminum, resulting in pits with a depth of about 10 nm.

[0110] Example 3 - Coating of Glass Articles Treated with Aqueous Treatment Medium Samples

[0111] Let ion exchange Glass pharmaceutical sample bottles were etched in aqueous treatment medium samples 1, 25 and 26 at room temperature for 24 hours. Aqueous treatment medium samples 25 and 26 were made according to the procedure described in Example 1. The compositions of aqueous treatment medium samples 1, 25 and 26 are listed in Table 3.

[0112] Table 3: Composition of aqueous treatment media samples

[0113] Sample No. Citric acid(M) NaCl(M) <![CDATA[AlCl3(M)]]> <![CDATA[NH4HF2(M)]]> Sample 1 1.0 0.0 0.0 0.026 Sample 25 1.0 0.25 0.0 0.026 Sample 26 1.0 0.0 0.25 0.026

[0114] Make the etched sample bottle in the Nexolve TM 3 wt% CP1 TM Dip coating in polyimide solution. CP1 TM is a colorless fluorinated polyimide that is soluble in the fully imidized form. In addition, the etched sample bottle was made in a solution containing 3 wt% CP1 TM The diameter of silica nanoparticles is about 20nm, which is smaller than CP1. TM The loading amount of CP1 was 5 wt %. In addition, a reference sample bottle that was not etched with aqueous treatment medium was coated with 3 wt % CP1. TM solution and 3 wt% CP1 TM The coated sample bottles were cured at 360°C for 15 minutes.

[0115] The friction coefficient of the coated sample bottle is measured under the 10*10N scratch test conditions. Specifically, two sample bottles are mounted vertically relative to each other. One sample bottle is moved laterally at 45° while applying a specific normal force to the other sample bottle, and then the friction coefficient is measured. The friction coefficient is measured at 50% relative humidity and ambient temperature. The normal force is 10N and the scratch is repeated 10 times. The friction coefficient data of each sample bottle is plotted on Fig.13In addition, the average friction coefficient of each sample bottle is listed in Table 4. The sample bottle etched with the aqueous treatment medium has a lower friction coefficient than the reference sample bottle.

[0116] Table 4: Friction coefficient

[0117] Sample No. CP1 coating <![CDATA[CP1 + SiO2 coating]]> Reference(none) 0.390 0.410 Sample 1 0.315 0.356 Sample 25 0.325 0.366 Sample 26 0.353 0.354

[0118] The present invention is directed to various embodiments of aqueous treatment media, methods of making aqueous treatment media, and methods of using aqueous treatment media. In embodiments, the aqueous treatment medium comprises water, acids, salts, fluorine-containing compounds, and silica, wherein the aqueous treatment medium is saturated with silica. The aqueous treatment medium is operable to impart a texture to the surface of a glass article treated with the aqueous treatment medium. The texture can enhance the adhesion of the coating to the glass article and can reduce the coefficient of friction of the glass article.

[0119] Those skilled in the art will appreciate that various changes and modifications may be made to the embodiments described herein without departing from the spirit and scope of the claimed object. This specification intends to cover any changes and modifications of the various embodiments described herein that fall within the scope of the appended claims and their equivalents.

Claims

1. An aqueous treatment medium, comprising: water; an acid selected from the group consisting of HCl, HBr, HNO3, H2SO4, H2SO3, H3PO4, H3PO2, HOAc, citric acid, tartaric acid, ascorbic acid, EDTA, methanesulfonic acid, toluenesulfonic acid, and combinations thereof, wherein the concentration of the acid in the aqueous treatment medium is 0.5 M to 1.5 M; Salts, wherein the concentration of the salt in the aqueous treatment medium is greater than 0 M to 2 M; A fluorine-containing compound selected from the group consisting of HF, NaF, NH4HF2, and combinations thereof, wherein the concentration of the fluorine-containing compound in the aqueous treatment medium is 0.026 M to 0.26 M; and Silica, wherein the aqueous treatment medium is saturated with silica.

2. The aqueous treatment medium of claim 1, wherein the acid comprises citric acid.

3. The aqueous treatment medium of claim 1, wherein the salt comprises an alkali metal salt.

4. The aqueous treatment medium of claim 1, wherein the salt comprises sodium chloride.

5. The aqueous treatment medium of claim 1, wherein the salt comprises aluminum chloride.

6. The aqueous treatment medium of claim 1, wherein the salts comprise sodium chloride and aluminum chloride.

7. The aqueous treatment medium of claim 6, wherein the aluminum to sodium ratio is from 1:1 to 3:

1.

8. The aqueous treatment medium of claim 1, wherein the fluorine-containing compound comprises NH4HF2.

9. The aqueous treatment medium of claim 1, wherein the acid comprises citric acid, the salt comprises sodium chloride, aluminum chloride, or a combination thereof, and the fluorine-containing compound comprises NH4HF2.

10. A method for treating a glass article, the method comprising contacting a surface of a glass article with an aqueous treatment medium to form a treated surface of the glass article, wherein: The glass article comprises silica; The aqueous treatment medium comprises: water; an acid selected from the group consisting of HCl, HBr, HNO3, H2SO4, H2SO3, H3PO4, H3PO2, HOAc, citric acid, tartaric acid, ascorbic acid, EDTA, methanesulfonic acid, toluenesulfonic acid, and combinations thereof, wherein the concentration of the acid in the aqueous treatment medium is 0.5 M to 1.5 M; Salts, wherein the concentration of the salt in the aqueous treatment medium is greater than 0 M to 2 M; A fluorine-containing compound selected from the group consisting of HF, NaF, NH4HF2, and combinations thereof, wherein the concentration of the fluorine-containing compound in the aqueous treatment medium is 0.026 M to 0.26 M; and Silica, wherein the aqueous treatment medium is saturated with silica; and The aqueous treatment medium etches silica from and deposits silica onto the surface of the glass article.

11. The method of claim 10, wherein the glass article is formed from Type I Class A or Type I Class B glass in accordance with ASTM Standard E438-92.

12. The method of claim 10, wherein the glass article is formed from borosilicate glass.

13. The method of claim 10, wherein the glass article is an ion-exchange strengthened glass article comprising a surface compressive stress layer.

14. The method of claim 10, wherein the glass article is a glass container and comprises a sidewall at least partially surrounding an interior volume, the sidewall having an exterior surface.

15. The method of claim 14, wherein the aqueous treatment medium contacts the outer surface of the sidewall.

16. The method of claim 10, wherein contacting the glass article with the aqueous treatment medium is performed for a period of time ranging from 5 minutes to 72 hours.

17. The method of claim 10, wherein contacting the glass article with the aqueous treatment medium is performed at a temperature between ambient temperature and 50°C.

18. The method of claim 10, wherein the method further comprises rinsing at least the treated surface of the glass article with deionized water.

19. The method of claim 10, wherein the treated surface of the glass article comprises silica deposits having a height of greater than 0 nm to 20 nm and a diameter of greater than 0 nm to 50 nm.

20. The method of claim 10, wherein the method further comprises applying a low friction coating to the treated surface of the glass article.

21. A method for making an aqueous treatment medium, the method comprising: Heating a mixture to a temperature of 25°C to 95°C, the mixture comprising water; an acid selected from the group consisting of HCl, HBr, HNO3, H2SO4, H2SO3, H3PO4, H3PO2, HOAc, citric acid, tartaric acid, ascorbic acid, EDTA, methanesulfonic acid, toluenesulfonic acid, and combinations thereof; a fluorine-containing compound selected from the group consisting of HF, NaF, NH4HF2, and combinations thereof; and silica powder; allowing the mixture to cool to ambient temperature; Filtering out undissolved silica powder from the mixture; and One or more salts are added to the mixture to form the aqueous treatment medium.

22. The method of claim 21, wherein the water is deionized water.

23. The method of claim 21, wherein the acid comprises citric acid.

24. The method of claim 21, wherein the salt comprises an alkali metal salt.

25. The method of claim 21, wherein the salt comprises sodium chloride.

26. The method of claim 21, wherein the salt comprises aluminum chloride.

27. The method of claim 21, wherein the salts comprise sodium chloride and aluminum chloride.

28. The method of claim 27, wherein the aluminum to sodium ratio is 1:1 to 3:

1.

29. The method of claim 21, wherein the fluorine-containing compound comprises NH4HF2.

30. The method of claim 21, wherein the silica powder comprises silica particles having a particle size of 100 nm to 1000 nm.

31. The method of claim 21, wherein the acid comprises citric acid, the salt comprises sodium chloride, aluminum chloride, or a combination thereof, and the fluorine-containing compound comprises NH4HF2.

32. The method of claim 21, wherein the concentration of the acid in the aqueous treatment medium is 0.5 M to 1.5 M.

33. The method of claim 21, wherein the concentration of the salt in the aqueous treatment medium is greater than 0 M to 2 M.

34. The method of claim 21, wherein the concentration of the fluorine-containing compound in the aqueous treatment medium is from 0.026M to 0.26M.

35. The method of claim 21, wherein the aqueous treatment medium is saturated silica.

Citation Information

Patent Citations

  • Glass containers with improved strength and improved damage tolerance

    US20140151321A1

  • Glass articles with low-friction coatings

    US9918898B2